Analysis of Potential Motor Vehicle Tax Opportunities and Motor Vehicle Title Transfer Fee Opsens: Study in Central Lombok Regency - Hariadi, Sheryl Yasina; Hilendri, Baiq Anggun; Ridhawati, Rini (International Journal of Business and Applied Economics, 2024)
This research aims to map regional revenue potential when the Opsen PKB and Opsen BBNKB schemes are implemented in the Central Lombok Regency. Quantitative methods using data on the number of motorized vehicles, regional tax targets and realization, gross regional domestic product, and regional income are used in this research to measure tax performance and analyze potential tax opportunities. The results of this research are that the PKB revenue ratio is in the medium category. BBNKB is in the low category, tax effort PKB and BBNKB are in the very low category, the elasticity ratio of both shows elastic results, the PKB collection ratio has an average of 7%, and BBNKB 6%, the effectiveness ratio of PKB is in the effective category,. BBNKB is in the quite effective category. The results of the analysis of potential tax opportunities show an increase in revenue for Central Lombok Regency.